Crowns in Pediatric Dentistry: A Review - Sonali Bhuyan1 , Susant Mohanty2 , Antarmayee Panigrahi3, Mrinali Shukla1 , Sulagna Pradhan1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Dental caries is the most common chronic disease of childhood. To treat such severely destructed teeth is achallenge for most pediatricians because of three important considerations-patient’s behavioral management,tooth structure preservation, and satisfaction of parents. Various efforts have been made for full coveragerestorations in pediatric dentistry. Every material has its own merits and demerits. Various options availablenowadays are stainless steel crowns and its various forms like strip crowns, zirconium crowns, etc.